2020
DOI: 10.1088/1674-1056/ab7da1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect and critical behavior of the Mn-rich itinerant material Mn3GaC with enhanced ferromagnetic interaction*

Abstract: We revisit the reversible magnetocaloric effect of itinerant ferromagnet Mn3GaC near the ferromagnetic to paramagnetic phase transition by adopting the experimental and theoretical methods and critical behavior of Mn-rich Mn3GaC with an enhanced FM interaction. Landau theory model cannot account for temperature dependent magnetic entropy change which is estimated from thermal magnetic methods only considering magnetoelastic coupling and the electron–electron interaction, apart from molecular mean-field model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The experimental value of the Mn-Mn distance is determined for alloys, in which magnetic order is considered in terms of direct exchange interactions. Previous studies suggested the presence of different mechanisms in antiperovskites, such as the Ruderman-Kittel-Kasuya-Yosida (RKKY) interactions [38,39]. Unlike the previously mentioned Mn-based compounds, Mn 4 N crystallizes in the antiperovskite type of structure and shows a ferrimagnetic behaviour, which can lead to a better match of the experimentally estimated critical distance between Mn atoms.…”
Section: Structural Propertiesmentioning
confidence: 89%
“…The experimental value of the Mn-Mn distance is determined for alloys, in which magnetic order is considered in terms of direct exchange interactions. Previous studies suggested the presence of different mechanisms in antiperovskites, such as the Ruderman-Kittel-Kasuya-Yosida (RKKY) interactions [38,39]. Unlike the previously mentioned Mn-based compounds, Mn 4 N crystallizes in the antiperovskite type of structure and shows a ferrimagnetic behaviour, which can lead to a better match of the experimentally estimated critical distance between Mn atoms.…”
Section: Structural Propertiesmentioning
confidence: 89%
“…[1][2][3][4][5][6][7] The novel solid-state refrigeration technology based on the magnetocaloric effect (MCE) is one of the most promising replacements for conventional refrigeration technologies because of its high efficiency and non-emission of pollutants. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The MCE is the thermodynamic response of the magnetic material to an applied magnetic field, meaning that the magnetic moment transforms from ordered to disordered (or ordered to ordered) during the imposition of an applied magnetic field, resulting in a change in magnetic entropy. [24] The maximum magnetic entropy changes (−∆S max M ) generally appear near the magnetic phase transition temperature, so the magnetic phase transition is strongly correlated with the MCE.…”
Section: Introductionmentioning
confidence: 99%